Massive Codesign A Proposal for a Collaborative Design Framework - Meroni, Anna (Design International - Open access, 2018)
"This book focuses on ""massive codesign"": the idea that multiple and/or numerous participants having different voices collaborate in a design process broken down into different steps and formats and resulting in a relevant and diversified amount of data. Services, strategies and scenarios are presented as the main field of application: these are complex items that demand complex processes be tackled, processes in which it is necessary to involve a variety of players who are largely interdependent and therefore who must collaborate in order to achieve any goal. The book essentially makes two main contributions: a ""Collaborative Design Framework"" to identify and structure codesign activities, methods and tools within massive creative processes; a ""set of quick lessons learnt"" to provide guidance to the conception and organisation of other massive creative processes. The whole book is oriented at practice: it discusses codesign activities from the designer's point of view, detailing issues such as process from beginning to end, activity flow, manipulability of tools, roles and rules for participants and many others. It is intended as a support for designers dealing in massive codesign processes and aims towards improved results."